المعالجات القانونية لمبدأ التقاضي على درجتين في المادة الإدارية - قديري, عمار (My University, 2023)
إن التقاضي على درجتين من المبادئ الأساسية لكل نظام قضائي محكم ومنصف، ووسيلة فعالة لتحقيق العدالة وضمانة قوية للوصول إلى المحاكمة العادلة، كما أنها من بين الضمانات التي لا غنا عنها مهما كانت العناية في اختيار القضاة عالية ومهما كانت الرقابة المفروضة عليهم كافية. من الواضح أن دستور 1996 أراد أن يكرس للازدواجية وفق النموذج الفرنسي لكن بقي الهيكل القضائي مبتورا دون محاكم استئنافية، إلى غاية التحول الذي جاء به التعديل الدستوري لسنة 2020 برفع المبدأ إلى مصاف المبادئ الدستورية وما تبعه من حركة في التشريع . إن الارتفاع بالمبدأ إلى مبدأ دستوري نجم عنه استحداث محاكم إدارية للاستئناف وبذلك اكتملت درجات السلم القضائي الإداري وأصبح المبدأ مكتملا هيكليا. إن إحداث محاكم إدارية للاستئناف فرض إعادة توزيع الاختصاص بين جهات القضاء الإداري، ومن دون شك سيساهم ذلك في تقليص الضغط المفروض على مجلس الدولة وسيساهم ذلك في تفرغ هذا الأخير لمهمته الأساسية كجهة مقومة. Litigation on two levels is one of the basic principles of every court system, which is fair and airtight, and an effective means of achieving justice and a strong guarantee for access to a fair trial. It is clear that the constitution1996wanted to enshrine duality according to the French model, but the judicial structure remained truncated without appeal courts, until the transformation brought about by the constitutional amendment of 2020 by raising the principle to the ranks of constitutional principles and the subsequent movement in legislation. The elevation of the principle to a constitutional principle resulted in the creation of administrative courts of appeal, and thus the degrees of the administrative judicial ladder were completed, and the principle became structurally complete. The creation of administrative courts of appeal imposed a redistribution of jurisdiction among the administrative judiciary authorities, and without a doubt this will contribute to reducing the pressure imposed on the State Council, and this will contribute to the latter's devotion to its primary mission as a regulating body.
مذكرة ماستر
Keywords: التقاضي على درجتين – محاكم إدارية للاستئناف – الاختصاص – مجلس الدولة; Litigation on two levels- administrative courts of appeal - jurisdiction among - the State Council